Fly ash-regenerated calcium source cementing material and preparation method thereof
By using fly ash and egg shells as composite precursor materials, alkali-excited gelling materials are prepared under alkali solution excitation, which solves the recycling and utilization of solid waste and achieves efficient and environmentally friendly resource utilization and environmental protection.
Patent Information
- Application Number
- CN202311000375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively recycle and utilize solid waste fly ash and egg shells, resulting in waste of resources and environmental pollution.
Fly ash and egg shells are used as composite precursor materials to prepare alkali-excited gelling materials under alkali solution excitation, and NaOH and Na2SiO3 are used as alkali-exciting agents.
The efficient recycling and utilization of fly ash and egg shells is achieved. The prepared gelled materials have high strength, low energy consumption, low emissions, and can effectively cure and stabilize the heavy metals in the waste, with good economic and social benefits.
Smart Images

Figure CN119461905A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a fly ash-regenerated calcium source cementitious material and a preparation method thereof. Background Art
[0002] Alkali-activated cementitious materials are a new type of low-carbon and environmentally friendly cementitious materials that have been developed. Alkali-activated cementitious materials activate the active substances in raw materials such as silicate and aluminate to form a cementitious system. Compared with traditional silicate cementitious materials, the preparation process is simple, the energy consumption is low, the emission is small, the waste utilization rate is high, and it has high strength and good durability. The raw material mixture of alkali-activated cementitious materials is mainly materials with relatively high volcanic ash activity, such as fly ash, silica fume and other solid wastes. Therefore, it can effectively utilize solid wastes and reduce resource waste. Common solid wastes include fly ash, coal gangue, bottom slag, etc.
[0003] Fly ash is a byproduct of coal combustion. During the combustion process, the coal and other impurities that are not completely burned are processed and separated, and the fine particles in the coal ash become fly ash. Fly ash is mainly composed of inorganic substances, including silicates, oxides, hydroxides, aluminates, calcium compounds, etc. It also contains a small amount of organic matter and heavy metal elements, such as cadmium, lead, mercury, etc. Fly ash particles are fine, porous and spherical. Direct exposure to high concentrations of fly ash particle suspensions or long-term exposure to its waste may have a negative impact on human health. Inhalation of fly ash particles may cause respiratory inflammation, dyspnea and other respiratory problems. Long-term exposure to fly ash containing heavy metals may increase the risk of certain cancers and neurological diseases. If not properly handled or discharged, fly ash may also pollute soil, water and air; eggshell refers to the outer hard shell of an egg, which is mainly composed of calcium, accounting for about 95% of the shell weight. Other components include carbonates, phosphates, magnesium, sodium and other trace elements. Eggshell is a natural degradable material with little impact on the environment. If eggshells are properly recycled and composted, they can provide organic matter and calcium to the soil. However, although eggshells are naturally degradable, if they are discarded in the natural environment, they will decompose slowly and have a certain impact on wildlife and aquatic ecosystems. With the increase in people's income and the improvement of living standards, the consumption of eggs has increased year by year. Although some eggshells are recycled, such as animal feed and plant waste, most eggshells are not used due to the limitations of reuse and economic effects. About 4 million tons of eggshells are directly discarded each year, resulting in a huge waste of resources and causing certain pollution to the environment. Therefore, how to reasonably and fully utilize the waste eggshell resources has become an urgent problem to be solved. Summary of the invention
[0004] In view of the problem of how to effectively recycle solid waste, the first purpose of the present invention is to provide a fly ash-regenerated calcium source cementitious material, the second purpose is to provide a method for preparing the above-mentioned alkali-activated cementitious material, and the third purpose is to provide the application of the above-mentioned alkali-activated cementitious material. The alkali-activated cementitious material described in the present invention completely uses solid waste fly ash and domestic waste egg shells as composite precursor materials, and then prepares the cementitious material under the stimulation of an alkali solution. It has the advantages of a wide source of raw materials, simple preparation, and high strength. It can fully recycle solid waste, has low energy consumption and low emissions, and can effectively solidify and stabilize heavy metals in waste, which has positive significance for the ecological environment and human health.
[0005] In order to achieve the above object, the specific scheme adopted by the present invention is:
[0006] A fly ash-regenerated calcium source gelling material comprises a composite precursor material and an alkali activator; the composite precursor material is composited from fly ash and egg shells; the alkali activator comprises one or both of NaOH and Na2SiO3 solution.
[0007] In the cementitious material of the present invention, based on the total mass of the composite precursor material, the mass percentage of the fly ash is 80%-95%, for example, 80%, 85%, 90%, 95% or any value therebetween, preferably 85%-90%; the mass percentage of the eggshell is 5%-20%, for example, 5%, 10%, 15%, 20% or any value therebetween, preferably 10%-15%.
[0008] In the gelling material of the present invention, the mass of the alkaline activator accounts for 60% of the total mass of the composite precursor material, wherein the mass ratio of NaOH to Na2SiO3 is 1:0-1:3, for example, 1:0, 1:0.3, 1:1, 1:3, preferably 1:1-1:3.
[0009] In a second aspect, the present invention provides a method for preparing the fly ash-regenerated calcium source cementitious material according to the first aspect, comprising the following steps: (1) taking 80-95 parts by weight of fly ash and 5-20 parts by weight of egg shell, stirring and mixing them at room temperature and dry conditions to obtain a composite powder; (2) mixing and stirring a NaOH solution accounting for 50% of the composite powder and a Na2SiO3 solution at a weight ratio of 1:0-1:3 to obtain an alkaline activator solution; (3) mixing the composite powder obtained in step (1) with the alkaline activator solution obtained in step (2) and stirring with a pure slurry mixer to obtain a gelling material; (4) Pour the cementitious material slurry into the mold, compact it on a cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould it and take it out, and perform curing at a curing temperature of 20±3℃.
[0010] The beneficial effects of the present invention are:
[0011] (1) The preparation process of the present invention is simple, no heating and calcination is required in the preparation process, no CO2 emission, low energy consumption, low preparation cost, and significant economic and social benefits.
[0012] (2) The present invention can recycle fly ash waste, and the egg shells used are domestic waste, which solves the problem of large-scale accumulation and treatment and reduces its impact on the surrounding environment.
[0013] (3) The present invention utilizes solid waste and domestic garbage to prepare cementitious materials, the strength of which can meet the requirements of engineering construction and can effectively replace silicate cement.
[0014] (4) The present invention uses egg shells as the calcium source of the cementitious material, which can significantly improve the strength of the alkali-activated fly ash cementitious material. Egg shells are a renewable resource, which can not only reduce the pollution of domestic waste, but also improve the utilization rate of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 2 is the XRD spectrum of the gelling material 28d of different implementation cases.
[0016] Figure 2 It is the infrared spectrum of the cementitious material 28d of different implementation examples.
[0017] Figure 3 : are SEM images of the cementitious material 28d of different implementation cases; among them, (a) is the SEM image of the cementitious material 28d obtained in Example 1, (b) is the SEM image of the cementitious material 28d obtained in Comparative Case 2, (c) is the SEM image of the cementitious material 28d obtained in Example 3, and (d) is the SEM image of the cementitious material 28d obtained in Comparative Case 4. DETAILED DESCRIPTION
[0018] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0019] The fly ash used in the following embodiments of the present invention is a powder with a particle size of less than 0.2 mm, and its chemical composition is shown in Table 1.
[0020] The egg shells used were from an egg shell power generation processing plant, and their chemical composition is shown in Table 2.
[0021] The alkaline activators used are NaOH and water glass, wherein the NaOH reagent used is a white uniform granular or flaky solid, and its chemical composition is shown in Table 3; the water glass used is SP50 water glass, with a modulus of 2.3, a colorless, slightly colored, transparent viscous liquid, and a density of 1.46-1.51 g / cm 3 (20℃), the main components are SiO2 and Na2O.
[0022] Table 1 Chemical composition of fly ash (%)
[0023] Table 2 Chemical composition of egg shell (%) element CaO <![CDATA[P2O5]]> <![CDATA[SiO2]]> MgO <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[Na2O]]> Cl I content 96.92 0.64 0.22 0.49 0.42 0.16 0.21 0.26 0.16
[0024] Table 3 Chemical composition of NaOH reagent (%) Element NaOH <![CDATA[Na2CO3]]> <![CDATA[SO4]]> <![CDATA[PO4]]> Al Ca Cl N K Fe Quality content 96.0 1.5 0.5 0.1 0.2 0.5 0.5 0.1 0.5 0.1
[0025] Example 1
[0026] A fly ash-regenerated calcium source cementitious material, the preparation of which comprises the following steps: 1) Take 95 parts by weight of fly ash and 5 parts by weight of egg shell, stir and mix them at room temperature and dry conditions to obtain a composite powder; 2) mixing NaOH solution accounting for 60% of the composite powder and Na2SiO3 solution at a mass ratio of 1:1 and stirring evenly to obtain an alkaline activator solution; 3) mixing the composite powder obtained in step 1) with the alkaline activator solution obtained in step 2) and stirring with a pure slurry mixer to obtain a gelling material; 4) Pour the cementitious material slurry into the mold, compact it on the cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould and take it out, and cure it at a curing temperature of 20±3℃.
[0027] Example 2
[0028] A fly ash-regenerated calcium source cementitious material, the preparation of which comprises the following steps: 1) Take 90 parts by weight of fly ash and 10 parts by weight of egg shell, stir and mix at room temperature and dry conditions to obtain a composite powder; 2) mixing NaOH solution accounting for 60% of the composite powder and Na2SiO3 solution at a weight ratio of 1:1 and stirring evenly to obtain an alkaline activator solution; 3) mixing the composite powder obtained in step 1) with the alkaline activator solution obtained in step 2) and stirring with a pure slurry mixer to obtain a gelling material; 4) Pour the cementitious material slurry into the mold, compact it on the cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould and take it out, and cure it at a curing temperature of 20±3℃.
[0029] Example 3
[0030] A fly ash-regenerated calcium source cementitious material, the preparation of which comprises the following steps: 1) Take 85 parts by weight of fly ash and 15 parts by weight of egg shell, stir and mix at room temperature and dry conditions to obtain a composite powder; 2) mixing NaOH solution accounting for 60% of the composite powder and Na2SiO3 solution at a weight ratio of 1:1 and stirring evenly to obtain an alkaline activator solution; 3) mixing the composite powder obtained in step 1) with the alkaline activator solution obtained in step 2) and stirring with a pure slurry mixer to obtain a gelling material; 4) Pour the cementitious material slurry into the mold, compact it on the cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould and take it out, and cure it at a curing temperature of 20±3℃.
[0031] Example 4
[0032] A fly ash-regenerated calcium source cementitious material, the preparation of which comprises the following steps: 1) Take 80 parts by weight of fly ash and 20 parts by weight of egg shell, stir and mix at room temperature and dry conditions to obtain a composite powder; 2) mixing NaOH solution accounting for 60% of the composite powder and Na2SiO3 solution at a weight ratio of 1:1 and stirring evenly to obtain an alkaline activator solution; 3) mixing the composite powder obtained in step 1) with the alkaline activator solution obtained in step 2) and stirring with a pure slurry mixer to obtain a gelling material; 4) Pour the cementitious material slurry into the mold, compact it on the cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould and take it out, and cure it at a curing temperature of 20±3℃.
[0033] The following comparative cases 1-4 are based on embodiments 1-4 by changing relevant parameters and comparing relevant performances.
[0034] Comparative Case 1
[0035] The weight ratio of NaOH solution accounting for 60% of the composite powder to Na2SiO3 solution was replaced to 100:0, and the remaining operations were the same as those in Example 2.
[0036] Comparative Case 2
[0037] The weight ratio of NaOH solution and Na2SiO3 solution, which account for 60% of the composite powder, was replaced with 75:25, and the remaining operations were the same as those in Example 2.
[0038] Comparative Case 3
[0039] The weight ratio of NaOH solution and Na2SiO3 solution, which account for 60% of the composite powder, was replaced with 25:75, and the remaining operations were the same as those in Example 2.
[0040] Comparative Case 4
[0041] The weight ratio of NaOH solution accounting for 60% of the composite powder to Na2SiO3 solution was replaced to 0:100, and the remaining operations were the same as those in Example 2.
[0042] The strength of the cementitious materials in the above-mentioned embodiments and comparative examples were tested with reference to JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", and the results are shown in Table 4.
[0043] Table 4 Strength test results of different alkali-activated cementitious materials
[0044] Among them, the XRD characteristics of the new environmentally friendly gelling material 28d of Example 3, Comparative Case 4, Comparative Case 8 and Comparative Case 12 are as follows: Figure 1 As shown in the figure, it can be seen that the products of fly ash-eggshell geopolymer cementitious material after hydration and hardening are mainly mullite, calcite, hydrated calcium silicate, hydrated calcium aluminosilicate and ettringite, as well as quartz residues in the raw materials.
[0045] The infrared spectra of the new environmentally friendly gelling material 28d of Example 3, Comparative Case 4, Comparative Case 8 and Comparative Case 12 are as follows: Figure 2 As shown in the figure, it can be seen that the product corresponding to the shrinkage vibration peak of the hydration product is consistent with the XRD spectrum, and the final components of the gelling material include reaction products (such as CASH gel) and unreacted fly ash powder.
[0046] The scanning electron microscope images of the new environmentally friendly gelling material 28d of Example 3 and Comparative Example 4 are as follows: Figure 3 As shown in the figure, it can be clearly seen that the fly ash-eggshell geopolymer cementitious material is hydrated to generate calcite, calcium aluminosilicate and calcium aluminosilicate gel, and the calcium aluminosilicate gel fills the pores and bonds various products together. Figure 3 It can be seen Figure 1 The microscopic morphology of the corresponding product in further verified the composition of the hydration product.
[0047] It can be concluded from Table 5 that the fly ash-eggshell geopolymer cementitious material has good compressive properties when the fly ash content is within the range of 10%-15%. When the mass ratio of fly ash to eggshell is 85:15 and the mass ratio of NaOH solution to Na2SiO3 solution is 50:50, the compressive properties of the cementitious material are the best, and the 28d strength can reach 33.93MPa. For the same eggshell content, the compressive properties of the cementitious material are the best when the mass ratio of NaOH solution to Na2SiO3 solution is 50:50.
[0048] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A fly ash-regenerated calcium source cementitious material, characterized in that: It comprises a composite precursor material and an alkali activator; the composite precursor material is composited from fly ash and egg shell; the alkali activator comprises one or two of NaOH and Na2SiO3 solution.
2. The gelling material according to claim 1, characterized in that: The composite precursor material is composed of fly ash and egg shells; based on the total mass of the composite precursor material, the mass percentage of the fly ash is 80%-95%, and the mass percentage of the egg shell is 5%-20%.
3. The gelling material according to claim 1, characterized in that: The mass percentage of the fly ash is 80%-95%, and the mass percentage of the egg shell is 5%-20%.
4. The gelling material according to claim 1, characterized in that: The mass of the alkaline activator accounts for 60% of the total mass of the composite precursor material, wherein the mass ratio of NaOH to Na2SiO3 is 1:1-1:
4.
5. The method for preparing a fly ash-regenerated calcium source cementitious material according to any one of claim 1, characterized in that: The steps include: (1) 80 to 95 parts by weight of fly ash and 5 to 20 parts by weight of fly ash are mixed and stirred at room temperature and in a dry state to obtain a composite powder; (2) mixing and stirring a NaOH solution and a Na2SiO3 solution to obtain an alkaline activator solution; the mass ratio of NaOH to Na2SiO3 in the alkaline activator solution is 1:1-1:4, and the sum of the mass of NaOH and Na2SiO3 accounts for 60% of the total mass of the composite powder; (3) mixing the composite powder obtained in step (1) with the alkaline activator solution obtained in step (2) and stirring with a pure slurry mixer to obtain a gelling material; (4) Pour the cementitious material slurry into the mold, compact it on a cement mortar compaction table for 0.5 to 5 minutes, let it stand for 1 to 3 days, then demould it and take it out, and perform curing at a curing temperature of 20±3℃.
6. The preparation method according to claim 6, characterized in that: Fly ash and egg shells are used to prepare composite powder, wherein the mass ratio of the fly ash to the egg shells is 85:15; and the mass ratio of NaOH to Na2SiO3 in the alkali excitation solution is 1:
3.
7. Use of the cementitious material according to any one of claims 1 to 4 or the cementitious material prepared by the preparation method according to any one of claims 5 to 6 in preparing building materials.
8. A method for utilizing industrial solid waste and domestic garbage waste, characterized in that: The industrial solid waste is fly ash produced by coal burning, and the domestic garbage waste is egg shells; The utilization method is to use the industrial solid waste and domestic garbage waste as raw materials to prepare a cementitious material so as to realize resource utilization. The specific process is: fly ash and egg shells are compounded to prepare a composite powder, and then the composite powder is mixed and stirred with an alkaline activator solution to obtain a cementitious material; Wherein, the composite powder comprises 80-95 parts by weight of fly ash and 5-20 parts by weight of egg shell; The alkaline activator includes NaOH and Na2SiO3, the mass ratio of NaOH to Na2SiO3 is 1:1-1:4, and the sum of the mass of NaOH and Na2SiO3 accounts for 60% of the total mass of the composite powder.